Ilmu Kimia Tumbuhan Lauraceae Indonesia : XI. Alkaloid Aporfin dan Oksoaporfin dari Litsea excelsa. - Euis Holisotan Hakim; Sjamsul Arifin Achmad; Buchari Buchari; Sidharta Pramutadi (Journal of Mathematical and Fundamental Sciences, 1994)
The first chemical investigation on Litsea excelsa had been carried out in our laboratories. Three alkaloids had been isolated in this investigation, namely dicentrinone (I), nordicentrine (II), and norpredicentrine(III), and their identities were established through UV, 1H-NMR, 13C-NMR, and mass spectral evidence. Based on the co-occurrence of these three alkaloids in the single plant, a biogenetic oxidative sequence of these compounds may be proposed. This work will be of value for chemotaxonomy of the genus Litsea in particular, the Lauraceae in general. Penyelidikan kimia telah dilakukan untuk pertama kalinya terhadap tumbuhan Litsea excels. Tiga alkaloid telah ditemukan pada penyelidikan ini, yakni disentrinon (I), nordisentrin (II), dan norpredisentrin (III). Identitas ketiga senyawa ini ditetapkan berdasarkan data spektroskopi UV, 1H-NMR, 13C-NMR, dan spectrum massa. Dengan ditemukannya ketiga alkaloid secara bersama-sama dalam satu spesies tumbuhan ini, maka tahap oksidasi biogenesis ketiga senyawa dapat disarankan. Hasil penelitian ini berguna untuk kemotaksonomi genus Litsea khususnya, famili Lauraceae umumnya.